Regional determinants of work accidents in Italy - La Torre, Giuseppe; Verrengia, Giovanna; Saulle, Rossella; Kheiraoui, Flavia; Mannocci, Alice (La Medicina del Lavoro, 2017)
Objective: To identify the determinants of the regional differences in work injuries and mortality rates in Italy. Methods: Several linear regression models were built assessing the association between regional differences in work mortality and injury rates (as dependent variables) and socio-demographic factors (occupation and population) and variables describing alcohol consumption, mean age and availability of health care (as independent variables). Data sources are from ISTAT, INAIL, Health for All database and the national report Osservasalute. The analysis was carried out using data coming from all the Italian Regions. Results: The mean work mortality rate for the period 2006-2014 was 7.73 (DS 1.85) per 100,000 workers, while the injury rate was 4503.1 (DS 1413.5) per 100,000 workers. Socio-demographic variables and that related to health care (TC availability) were inversely associated with mortality rates, while for the work injury rates, significant associations with alcohol were found, while Gross domestic product and TC availability were inversely associated. Conclusions: The study pointed out the extreme heterogeneity between different geographical areas in the field of work injury, due to different socio-demographic and economic factors. In the future, health surveillance and work injury and mortality rates could be improved in areas at high risk.